International Labor Migration of Nepalese Women: Impact of their Remittances on Poverty Reduction - Chandra Bhadra (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2007)
The general objective of the study is to assess the impact of Women Migrant Workers' (WMWs) remittance in poverty reduction. The specific objectives are to investigate the financial aspect, to explore the human factors, and to examine WMWs' perception and preferences of the State's policy.
Keywords: F1; 330; International; Labor; Migration; Napalese; women; Impact; remittances; Poverty; reduction